2017
DOI: 10.1186/s13012-017-0571-2
|View full text |Cite
|
Sign up to set email alerts
|

Improving the adaptability of WHO evidence-informed guidelines for nutrition actions: results of a mixed methods evaluation

Abstract: BackgroundOver the past decade, the World Health Organization (WHO) has implemented a standardized, evidence-informed guideline development process to assure technically sound and policy-relevant guidelines. This study is an independent evaluation of the adaptability of the guidelines produced by the Evidence and Programme Guidance unit, at the Department of Nutrition for Health and Development (NHD). The study systematizes the lessons learned by the NHD group at WHO.MethodsWe used a mixed methods approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…The refinement of the current adaptation frameworks and the process of guideline adaptation would be an important step forward in changing health behaviour (of clinicians and general population alike) and the grand quest of improving global health. The idea of increasing the adaptability of guidelines has been a recent focus of WHO [ 35 ]. The effect of integrating adaptation methods such as optimized adaptation frameworks into the implementation sections of source recommendation documents (e.g., WHO guidelines) would be an important area to explore in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The refinement of the current adaptation frameworks and the process of guideline adaptation would be an important step forward in changing health behaviour (of clinicians and general population alike) and the grand quest of improving global health. The idea of increasing the adaptability of guidelines has been a recent focus of WHO [ 35 ]. The effect of integrating adaptation methods such as optimized adaptation frameworks into the implementation sections of source recommendation documents (e.g., WHO guidelines) would be an important area to explore in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The UNICEF (United Nations International Children Education Fund) and WHO (World Health Organization) recommend exclusive breastfeeding (EBF) for the first six months of life [1]. EBF is defined as feeding infants only breast milk and no other drink or food, not even water, for the first six months of life.…”
Section: Introductionmentioning
confidence: 99%
“…However, this view does not account for potential crowding out effects of UCTs, i.e., unintended negative effects of UCT provision on other types of financial assistance during disasters. [15]. They suggested that difficulties encountered in their evaluation may reflect limitations of GRADE guidance, specifically citing NRS, time requirements, and wording or strength of recommendations as issues.…”
Section: Examples Of Challengesmentioning
confidence: 99%